STATE-OWNED ENTERPRISES AND ENVIRONMENTAL DECISION-MAKING - Ganesan, Vignaa; Muhamad Varkkey, Helena (Malaysian Journal of Tropical Geography (MJTG), 2022)
When considering firms' environmental performance and decision-making processes, the literature has overwhelmingly focused on private firms. However, many firms involved in sectors linked to environmental exploitation are not private firms. In many natural resource-rich countries, state-owned enterprises (SOEs) control these resources. Many types of SOEs have different ownership and control structures, translating to varying emphases on profit. Therefore, this paper asks the question: do ownership and control structures of different types of SOEs influence their decision-making processes on the environment? To illustrate this, this paper uses a case study approach comparing two types of SOEs within the Malaysian palm oil sector: the people-oriented FELDA and the profit-oriented FGV. Despite similar market and governance conditions, the decisions taken by these SOEs resulted in opposite outcomes for the environment. FGV, with an ownership and control structure dominated by state and private investors, tended to take advantage of this structure to overlook environmental objectives in the pursuit of profits. On the other hand, FELDA, owned and controlled by the state and settler cooperatives, achieved both capital accumulation and environmental protection through environmentally- and socially conscious decision making. Hence, this paper argues that in the case of SOEs particularly, a firm's ownership and control structures can influence decision-making to either be positive or negative for the environment.